CHARACTERISATION OF EGG WHITE-IMPREGNATED ACTIVATED CARBON FOR CO2 ADSORPTION APPLICATION - Nur Syahirah Mohamed Hatta,; Farihahusnah Hussin,; Lai Ti Gew,; Mohamed Kheireddine Aroua, (Malaysian Journal of Science, 2024)
In this study egg white was used as a source of natural amino acids to modify the surface properties of palm shell activated carbon towards enhancing its CO2 capture performance. A simple impregnation method was employed for this purpose. Characterisation analysis was performed on the egg white-impregnated activated carbon to examine any changes on its surface properties prior to CO2 adsorption test. The modified adsorbent showed high thermal stability below 300°C and comprised of new amide functional group. Furthermore, the modified adsorbent exhibited 31% higher breakthrough time and maintained its CO2 adsorption capacity at 0.3 mmol/g in comparison to raw activated carbon, regardless of the reduction of surface area and micropore volume by 17% and 18% respectively. These findings provide evidence on the prospect of egg white-impregnated activated carbon for CO2 adsorption application which could pave the way for a new generation of affordable and eco-friendly adsorbents.